WORKING CAPITAL ANALYSIS AND ITS EFFECT ON ECONOMIC RENTABILITY IN FOOD AND BEVERAGE SUBSECTOR COMPANIES - Paul Eduard Sudjiman; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2019)
This study aims to determine the use of working capital in the form of current assets and current debt and its effect on profitability in the form of operating income before tax and total assets in companies listed on the Indonesia Stock Exchange. This research is a quantitative associative study and the period of this study was carried out for nine (9) years, namely 2009-2017. The population in this study were food and beverage subsector companies listed on the Indonesia Stock Exchange in the period 2009-2017 outside of companies from banking groups and other financial institutions. The sampling technique used was purposive sampling method and obtained a sample of 10 companies with a sample (n) = 90. The data used is secondary data from financial reports on the official site of the Indonesia Stock Exchange. The data analysis technique used was simple linear regression with significance of 0.05. Based on the results of data analysis using statistical tests conducted by the author, the correlation coefficient of Working Capital towards Economic Rentability has a very weak relationship seen from the value r = -0.163 and Significant value 0.124> 0.05 then Ho is accepted and Ha is rejected that Working Capital does not exist significant influence on economic rentability. Based on statistical analysis, it is known that the coefficient of determination shows R square = 0.027, which means that the figure shows the contribution of working capital factors to economic rentability of 2.7% while 97.3% is explained by other variables outside the research model.